Sex-Specific Changes in Cardiac Function and Electrophysiology During Progression of Adenine-Induced Chronic Kidney Disease in Mice - Valentina Dargam; Anet Sanchez; Aashiya Kolengaden; Yency Perez; Rebekah Arias; Ana M. Valentin Cabrera; Daniel Chaparro; Christopher Tarafa; Alexandra Coba; Nathan Yapaolo; Perony da Silva Nogueira; Emily A. Todd; et al. (Journal of Cardiovascular Development and Disease)
Chronic kidney disease (CKD) and cardiovascular disease (CVD) often co-exist, with notable sex-dependent differences in manifestation and progression despite both sexes sharing similar risk factors. Identifying sex-specific diagnostic markers in CKD-induced CVD could elucidate why the development and progression of these diseases differ by sex. Adult, C57BL/6J male and female mice were fed a high-adenine diet for 12 weeks to induce CKD, while control mice were given a normal diet. Adenine-treated males showed more severe CKD than females. Cardiac physiology was evaluated using electrocardiogram (ECG) and echocardiogram markers. Only adenine-treated male mice showed markers of left ventricular (LV) hypertrophy. Adenine males showed markers of LV systolic and diastolic dysfunction throughout regimen duration, worsening as the disease progressed. Adenine males had prolonged QTc interval compared to adenine females and control males. We identified a new ECG marker, Speak-J duration, which increased with disease progression and appeared earlier in adenine-treated males than in females. We identified sex-dependent differences in cardiac structure, function, and electrophysiology in a CKD-induced CVD mouse model, with adenine-treated males displaying markers of LV hypertrophy, dysfunction, and electrophysiological changes. This study demonstrates the feasibility of using this model to investigate sex-dependent cardiac differences resulting from CKD.